Menilik Diskursus Aurat Perspektif Al-Qur’an Pada Surah An-Nur Ayat 31: (Studi Analisis Tafsir Qur’an Karim Karya Mahmud Yunus Dan Tafsir An-Nur Karya Hasbi Ash-Shiddieqy) - Hanna Salsabila (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2022)
This study aims to discuss the concept of covering the genitals from the perspective of the Qur'an in Surah An-Nur verse 31 from the perspective of Karim's interpretation of the Qur'an and the interpretation of An-Nur. This research method is qualitative through literature study with a fiqh approach. This study concludes that there are similarities in the interpretation of women's genitalia according to the interpretation of the Qur'an Karim by Mahmud Yunus and the interpretation of An-Nur by Hasbi Ash-Shiddieqy, namely all parts of the body except the face, the palms of the hands and the soles of the feet, both of which refer to the opinion of Ibn Abbas. However, there is also a difference in the limits of a woman, according to the interpretation of the Qur'an Karim by Mahmud Yunus, a woman's half arm and half calf can be seen because these body parts are usually seen when working, this refers to the opinion of the Hanafi school. According to Hasbi Ash-Shiddieqy's interpretation of An-Nur, shaking hands with non-mahrams is not haram, because women's palms are not part of the genitals.